2021
DOI: 10.3892/mmr.2021.11906
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B2 inhibits lipopolysaccharide‑induced apoptosis by suppressing the Bcl‑2/Bax and NF‑κB signalling pathways in human umbilical vein endothelial cells

Abstract: Human umbilical vein endothelial cells (HUVECs) serve a critical role in maintaining normal vascular function. Lipopolysaccharide (LPS), which is released from pathogenic bacteria in the blood, induces HUVEC apoptosis and injury to cause vascular dysfunction and infectious vascular diseases. Procyanidin B2 (PB2) possesses numerous functions, including antioxidant, antitumor, anti-inflammatory and antiapoptosis effects, but the molecular mechanism is not completely understood. The present study investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Hence, low concentrations (5, 10, and 25 μM) of PB2 were used in the study to detect its protective effects under heat exposure. This study found that 5, 10, and 25 μM of PB2, effectively dose-dependently, alleviated the decline in cell viability induced by high temperature, which is consistent with the research results, which suggest that PB2 can ameliorate the reduction in neuronal cell viability caused by cypermethrin [ 23 ] and defense the viability loss of human umbilical vein endothelial cells under lipopolysaccharide (LPS)-stimulated condition [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Hence, low concentrations (5, 10, and 25 μM) of PB2 were used in the study to detect its protective effects under heat exposure. This study found that 5, 10, and 25 μM of PB2, effectively dose-dependently, alleviated the decline in cell viability induced by high temperature, which is consistent with the research results, which suggest that PB2 can ameliorate the reduction in neuronal cell viability caused by cypermethrin [ 23 ] and defense the viability loss of human umbilical vein endothelial cells under lipopolysaccharide (LPS)-stimulated condition [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, there are also research findings that show that choline protects bovine mammary epithelial cells from HS-induced oxidative stress by inhibiting the expression and nuclear translocation of Nrf2 [ 46 ]. Similarly, PB2 was reported to protect mice cerebral cortex neurons from cypermethrin-induced oxidative stress by reducing Nrf2 expression and nuclear translocation [ 24 ]. The reason for this difference might be related to the intensity of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…LPS has been mostly used to study inflammatory responses 42 , 43 , 44 and recently reported to induce HUVEC apoptosis. 45 Recent studies have shown a close relationship between mitochondria and phagosomes following bacterial invasion. 46 Here, we observed that LPS strongly affected mitochondrial dynamics by targeting DRP1 and MFN1 in HUVECs, with circTMEM165 participating in the regulation of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment of the cells with PC markedly attenuated LPS-induced cytotoxicity and apoptosis. 37 The authors concluded that the potential molecular mechanism underlying the effects of PC was associated with the Bax/Bcl-2 and NF-κB signalling pathways. They suggested that PC may be useful as a novel therapeutic agent for infectious vascular diseases.…”
Section: Anti-atherosclerotic Effectsmentioning
confidence: 99%